Analysis of the Shifting Political Networks of Irman Gusman and Emma Yohana in the DPD Revote - Yuza Rahma Tullah; Asrinaldi; Doni Hendrik (JOELS: Journal of Election and Leadership, 2026)
The 2024 Revote (PSU) for the Regional Representative Council (DPD) of the Republic of Indonesia in West Sumatra presented unique electoral dynamics. This was triggered by a Constitutional Court decision that reinstated Irman Gusman into the contest, thereby shifting the position of incumbent Emma Yohana. This study aims to analyze the shift in political network support between Irman Gusman and Emma Yohana during the 2024 DPD revote in West Sumatra. The research employs a qualitative approach with a comparative case study type, combining Barnes’s social network typology and David Knoke’s (1994) seven indicators of political networks: centrality, prestige, network cohesion, structural equivalence, power-dependency relations, exchange relations, and network density. Data were collected through in-depth interviews, observation, and documentation studies, validated by triangulation. The results show that at the social network level, reconfiguration shifted from emotional and interest-based networks that previously supported Emma Yohana toward power networks deliberately managed through the nodes of Muhammadiyah, Bundo Kanduang, and community leaders to support Irman Gusman. At the political network level, this shift is reflected in simultaneous changes across Knoke’s seven indicators—centrality, prestige, cohesion, structural equivalence, power-dependency relations, exchange relations, and network density—which together signify the transfer of dominance and power relations from Emma Yohana to Irman Gusman. Thus, Barnes’s typology explains the types of networks at play, while Knoke’s indicators illustrate how these networks change, suggesting that the electoral shift in the revote was driven not merely by voter preference, but by the actors’ ability to reorganize political networks and consolidate new dependency nodes amid a public trust crisis in electoral integrity.